2013
DOI: 10.1002/ajmg.a.36348
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the clinical phenotype of patients with a ZDHHC9 mutation

Abstract: In 2007, 250 families with X-linked intellectual disability (XLID) were screened for mutations in genes on the X-chromosome, and in 4 of these families, mutations in the ZDHHC9 gene were identified. The ID was either isolated or associated with a marfanoid habitus. ZDHHC9 encodes a palmitoyl transferase that catalyzes the posttranslational modification of NRAS and HRAS. Since this first description, no additional patient with a ZDHHC9 mutation has been reported in the literature. Here, we describe a large fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 11 publications
2
41
0
Order By: Relevance
“…In these genes, we identified likely pathogenic variants in 39 of the 248 families (16%) and in 16 of the 157 families (10%), which together with the 24 families from these two cohorts that were resolved through this screen and were published earlier, 7, 20, 21, 23, 45, 46, 47, 48, 49, 50 account for 21 and 18% of the cohorts (for details, see Supplementary Tables 5 and 6). The variants include co-segregating protein truncating variants, in-frame deletions or missense changes and none of them were reported in 61 486 unrelated individuals (ExAC Browser).…”
Section: Resultsmentioning
confidence: 98%
“…In these genes, we identified likely pathogenic variants in 39 of the 248 families (16%) and in 16 of the 157 families (10%), which together with the 24 families from these two cohorts that were resolved through this screen and were published earlier, 7, 20, 21, 23, 45, 46, 47, 48, 49, 50 account for 21 and 18% of the cohorts (for details, see Supplementary Tables 5 and 6). The variants include co-segregating protein truncating variants, in-frame deletions or missense changes and none of them were reported in 61 486 unrelated individuals (ExAC Browser).…”
Section: Resultsmentioning
confidence: 98%
“…This altered autopalmitoylation level of DHHC9 is predicted to affect the palmitoylation of target proteins that might be involved in intellectual development [252]. By combining the value of next generation sequencing, it would be important to identify novel target proteins of DHHC9 associated with ID for providing molecular diagnosis and therapeutic treatment [249,253].…”
Section: Intellectual Disabilitymentioning
confidence: 99%
“…This is because, unlike neurodevelopmental disorders defined by behavioural impairments, they have a highly specific and known aetiology, common across all cases. Here, we studied a group of individuals with mutations in ZDHHC9, a rare recurrent cause of X-linked intellectual disability (XLID; Han et al, 2017;Raymond et al, 2007;Schirwani, Wakeling, Smith, Study, & Balasubramanian, 2018;Masurel-Paulet et al 2014). We previously found that individuals with ZDHHC9 mutations are susceptible to a combined phenotype of speech and language impairments, cognitive difficulties and Rolandic Epilepsy (RE; Baker et al, 2015).…”
Section: Introductionmentioning
confidence: 99%